1991
DOI: 10.1002/etc.5620100415
|View full text |Cite
|
Sign up to set email alerts
|

The acute toxicity of selected metals to the freshwater mussel, Anodonta imbecilis

Abstract: The mussel fauna of many North American waters is declining, probably due to a combination of factors. The factors may include channelization and impoundment of rivers where the mussels once thrived, as well as the influx of pesticides and metal pollution from surrounding watersheds. Much is known about the effects of metal pollution on zooplankton and aquatic insects, but little is known about the response of freshwater mussels. With more and more species of mussels being listed as threatened or endangered, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…While we had insufficient data to determine the relative sensitivity of listed species of mussels in our dataset, we determined that unlisted mollusks are more sensitive to metallic stressors and nonpolar narcotics but less sensitive to OPs and neurotoxicants compared to other taxa. Others have proposed the use of daphnids and zooplankton as surrogates for freshwater mussels [13,67]. The data for listed mussels included in the present study support these conclusions: All four toxicity records for listed mussels exposed to metallic stressors were in the first quartile of their respective SSD, toxicity for mussels exposed to nonpolar narcotics were in the first and second quartiles, and toxicity of the listed mussel exposed to an OP was in the upper quartile.…”
Section: Discussionsupporting
confidence: 82%
“…While we had insufficient data to determine the relative sensitivity of listed species of mussels in our dataset, we determined that unlisted mollusks are more sensitive to metallic stressors and nonpolar narcotics but less sensitive to OPs and neurotoxicants compared to other taxa. Others have proposed the use of daphnids and zooplankton as surrogates for freshwater mussels [13,67]. The data for listed mussels included in the present study support these conclusions: All four toxicity records for listed mussels exposed to metallic stressors were in the first quartile of their respective SSD, toxicity for mussels exposed to nonpolar narcotics were in the first and second quartiles, and toxicity of the listed mussel exposed to an OP was in the upper quartile.…”
Section: Discussionsupporting
confidence: 82%
“…First, the adequacy of CCCs, which were developed for protection of general aquatic life (USEPA, ; VDEQ, ), as protective levels for freshwater mussels has not been determined. Also, mussels are known to be sensitive to a variety of environmental metals, including Cd, Cu, Ni, Pb, and Zn (Havlik and Marking, ; Keller and Zam, ; Jacobson et al ., , ; Naimo, ; Keller et al ., ; Cope et al ., ; Wang et al ., ). In addition, other recent studies have found reasons for concern with metals as Clinch River water and sediment contaminants (Johnson et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…More than 200 acute observations for glochidia and juveniles were identified from 10 sources [13][14][15][16][17][18][19][20][21] Utterbackia imbecillis was the only species for which we found 50% lethal (LC50) or effect (EC50) concentrations for both in vivo-and in vitro-produced juveniles. A total of 22, 96-h juvenile tests [13,15,18] were conducted, with 12 tests of in vitro-produced juveniles and 10 tests of in vivo-produced juveniles.…”
Section: Acute Wqc/wqsmentioning
confidence: 99%